The effect of temperature and relative humidity for Aspergillus flavus BIO 2237 growth and aflatoxin production on soybeans - Broto, W. (2016)
Aspergillus flavus (A. flavus) producing aflatoxin frequently contaminates crops such as soybeans. The growth of this mold on soybeans and other foodstuffs is affected by temperature and relative humidity (RH). The aim of this study was to measure the growth of A. flavus BIO 2237 and aflatoxin production at different temperatures and RH. Aspergillus flavus BIO 2237 was isolated from Indonesia origin foodstuffs. Aspergillus flavus BIO 2237 was inoculated in Czapek Dox Agar (CDA) and soybeans for 10 days at a temperature of 20, 30, and 40oC with RH of 70, 80, and 90%. Aflatoxin analysis was conducted using RP-HPLC equipped with fluorescence detector and post column photochemical reactor. The limit of detection (LoD) for aflatoxin of B1, B2, G1, and G2 was 0.45, 0.26, 0.05, and 0.13 ng/mL (ppb), while their limit of quantification (LoQ) was 1.50, 0.88, 0.18 and 0.43 ng/mL (ppb) respectively. The maximum growth for A. flavus BIO 2237 in CDA and soybeans was reached at a temperature of 30oC with RH of 90%, and this was based on the highest diameter of colony and amount of cell mass formed in that condition. The maximum level of aflatoxin in contaminated soybeans was found at 999 ng/g (ppb), and this was produced at the same condition as its fungi’s growth. Aspergillus flavus BIO 2237 can not grow as well as produce aflatoxin in soybeans at high temperature (40ºC) with low RH (70%). There was a significant difference (sig<0.05) in aflatoxin content (AFB1, AFB2, AFG1, and AFG2) between temperature and RH, meanwhile the difference on the growth of A. flavus BIO 2237 in CDA and soybeans caused by RH